2020
DOI: 10.1186/s40635-020-00347-7
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular stroke volume assessed by pulmonary artery pulse contour analysis

Abstract: Background Stroke volume measurement should provide estimates of acute treatment responses. The current pulse contour method estimates left ventricle stroke volume. Heart-lung interactions change right ventricular stroke volume acutely. We investigated the accuracy, precision, and trending abilities of four calibrated stroke volume estimates based on pulmonary artery pulse contour analysis. Results Stroke volume was measured in 9 pigs with a pulmonary artery ultrasound flow probe at 5 and 10 cmH2O of PEEP an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Newer monitoring devices, which incorporate algorithms to estimate SV and CO from PA PWA , also fall short as they calculate these values over extended time periods rather than on the precise scale of cardiac cycles; therefore, they do not allow evaluation of beat-by-beat variability nor the effect of breathing on SV. Previous experimental studies have shown the possibility of detecting short-term changes in SV with PA pulse contour but a low beat-by-beat correlation with the reference method [ 3 ]. While echocardiography and Doppler techniques do offer beat-scale estimations of RVSV, their intermittent nature precludes their feasibility for continuous monitoring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Newer monitoring devices, which incorporate algorithms to estimate SV and CO from PA PWA , also fall short as they calculate these values over extended time periods rather than on the precise scale of cardiac cycles; therefore, they do not allow evaluation of beat-by-beat variability nor the effect of breathing on SV. Previous experimental studies have shown the possibility of detecting short-term changes in SV with PA pulse contour but a low beat-by-beat correlation with the reference method [ 3 ]. While echocardiography and Doppler techniques do offer beat-scale estimations of RVSV, their intermittent nature precludes their feasibility for continuous monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Estimation of left ventricle stroke volume (SV) through systemic arterial pulse wave analysis [ 1 ] is widely accepted in clinical practice [ 2 ]. The physiological principles used to estimate SV from arterial pulse wave analysis in the systemic circulation can also be applied to the pulmonary artery (PA) [ 3 ] to estimate the right ventricle (RV) SV (RVSV). Recent studies have underscored the role of RV and pulmonary circulation during hemodynamic instability situations [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A shortcoming of the PAC—stemming from the thermodilution technique - is its inability to report immediate changes in stroke volume. However, pulmonary pulse contour analysis with direct assessment of RV stroke volume is feasible ( Berger et al, 2020 ) and this limitation may be overcome by advanced PAC models with shorter thermodilution response times ( Bootsma et al, 2022 ).…”
Section: Advanced Bedside Techniques: Pulmonary Artery Catheterizatio...mentioning
confidence: 99%